(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
In today’s fast-growing time, science, technology are also growing rapidly. Progress in each area is taking a step forward. In particular, great changes, significant achievements are also being made in science. The delivery of each subject to students using new innovative technologies is one of the main requirements of today’s education.